Investigation of exopolysaccharide production capacity of thermophilic microorganisms isolated from Turkey - Yıldız, Songül Yaşar (My University, 2011)
TÜRKİYE KAYNAKLI TERMOFİLİK MİKROORGANİZMA-LARIN EKZOPOLİSAKKARİT ÜRETİM KAPASİTELERİNİN ARAŞTIRILMASI Mezofilik mikroorganizma kaynaklı biyopolimerlerin endüstriyel koşullarda özelliklerini koruyamamalarından dolayı son yıllarda yaşam koşulları endüstriyel koşullara benzeyen ekstremofilik mikroorganizmalara olan ilgi çok artmıştır. Ekstremofillerin yaşam ortamlarındaki ekstrem koşullara göre geliştirmiş oldukları farklı adaptasyon stratejilerinden biri ortama salgıladıkları, yüksek molekül ağırlıklı, farklı fizikokimyasal ve reolojik özelliklere ve bunlara bağlı yeni işlevselliğe sahip olan ekzopolisakkaritlerdir (EPS). Yüksek sıcaklıktaki ortamlarda yaşayan ekstremofiller olan termofiller ise, hızlı metabolizmaları ve yüksek sıcaklıktaki üretim gibi avantajları yüzünden EPSler için iyi bir kaynak oluşturmaktalardır. Bu doğrultuda gerçekleştirilmiş olan bu tez çalışmasında, Türkiye ve Bulgaristan’daki sıcak su kaynaklarından izole edilmiş 14 adet termofilik suşun EPS üretim kapasiteleri araştırılmış ve en iyi üretici suşlar belirlenmiştir. Bu suşların EPS üretim koşulları çalkalamalı ortamda optimize edilmiş ve daha sonra optimum şartlarda ve kontrollü biyoreaktör koşullarındaki biyokütle ve EPS üretim profilleri belirlenmiştir. Moleküler tanılama çalışmaları başlatılmış ve mikroorganizmaların Brevibacillus thermoruber suşları olduğu anlaşılmıştır. Üretilen polimerlerin mannoz monomerinden oluşmuş mannan homopolimeri olduğu anlaşılmıştır. Biyopolimerlerin termofilik mikroorganizmalardan elde edilen ilk mannan polimerleri olmaları dolayısı ile tez çalışmasının yayın değeri ve özgünlüğü yüksektir. Ekstremofiller, Termofilik mikroorganizmalar, Ekzopolisakkarit üretimi

INVESTIGATION OF EXOPOLYSACCHARIDE PRODUCTION CAPACITY OF THERMOPHILIC MICROORGANISMS ISOLATED FROM TURKEY Biopolymers of mesophilic microorganisms can hardly maintain their properties under industrial conditions and hence research has been directed to extremophiles which naturally survive under extreme environments commonly encountered in industry. These microorganisms have evolved many adaptation strategies to such extreme conditions one of which involves the production and excretion of high molecular weight exopolysaccharides (EPSs) having unique physicochemical and rheological properties with novel functionality. Thermofiles are extremophilic microorganisms living at high temperatures. They are considered as a valuable source for EPSs due to many advantages they provide such as their fast metabolism and enabling polymer production at high temperatures. Considering these facts, within the scope of this thesis, EPS production capacity of 14 thermophilic strains isolated from hots springs in Bulgaria and Turkey were investigated and good EPS producers were determined. Important fermentation parameters of selected EPS producers were optimized under shaking conditions and then the biomass and EPS production profiles of bioreactor cultures were determined under optimum conditions. Preliminary molecular identification studies revealed that the two selected isolates were Brevibacillus thermoruber strains. EPSs were characterized as mannan homopolymers composed of mannose residues. Since there are no reports on mannan producer thermophiles in literature yet, this thesis work confers high novelty warranting rapid publication. Key Words: Extremophiles, Thermophilic microorganisms, Exopolysaccharide production.
Keywords: Biyomühendislik; Ekstremofiller; Ekzopolisakkarit Üretimi; Termofilik Mikroorganizmalar